PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK TEMA 7 SUBTEMA 1 PADA SISWA KELAS IV SDN 036 TARAKAN - Tyaz Hasthishita; Kartini Kartini; Agustinus Toding Bua (Universitas Borneo Tarakan, 2020)
Abstract: This research purpose to produce learning media of scrapbooks in terms of the validity of the media, materials and practitioners as well as knowing the responses of IV-A students to scrapbook learning media. This research is a research and development (Research and Development). The research and development procedure uses the ADDIE model which consists of five stages namely Analysis, Design, Development, Implementation and Evaluation. The feasibility assessment of scrapbook learning media consists of media experts, material experts and practitioner experts. The subject of the research was class IV-A class year 2018/2019 SDN 036 Tarakan with 28 students. The results of the feasibility of the validation of the experts are 1) Media validation gets a percentage of 97%; 2) Material validation I obtained a percentage of 97.5%; 3) Material validation II obtains a percentage of 95%; and 4) Validation of practitioners obtains a percentage of 92.3%. All validation results get Very Eligible criteria. The results of student responses from limited trials in class IV-A class of academic year 2017/2018 obtained a percentage of 90% with very decent criteria, while the results of student responses from field trials in class IV-A class of academic year 2018/2019 gained a percentage of 95% with very decent criteria. Abstrak: Penelitian ini bertujuan untuk menghasilkan media pembelajaran berupa scrapbook yang ditinjau dari validitas media, materi dan praktisi serta mengetahui respon siswa IV-A terhadap media pembelajaran scrapbook. Penelitian ini merupakan penelitian dan pengembangan (Research and Development). Prosedur penelitian dan pengembangan menggunakan model ADDIE yang terdiri dari lima tahap yaitu Analysis, Design, Development, Implementation dan Evaluation. Penilaian kelayakan media pembelajaran scrapbook terdiri dari ahli media, ahli materi dan ahli praktisi. Subjek penelitian adalah siswa kelas IV-A angkatan tahun ajaran 2018/2019 SDN 036 Tarakan dengan jumlah siswa 28 orang. Hasil kelayakan dari validasi para ahli yaitu 1) Validasi media memperoleh persentase 97%; 2) Validasi materi I memperoleh persentase 97.5%; 3) Validasi materi II memperoleh persentase 95%; dan 4) Validasi praktisi memperoleh persentase 92.3%. Semua hasil validasi mendapatkan kriteria Sangat Layak. Hasil respon siswa dari uji coba terbatas di kelas IV-A angkatan tahun ajaran 2017/2018 memperoleh persentase 90% dengan kriteria sangat layak, sedangkan hasil respon siswa dari uji coba lapangan dikelas IV-A angkatan tahun ajaran 2018/2019 memperoleh persentase 95% dengan kriteria sangat layak.